Assessment of Quality of Life of Epileptic Patients in Ethiopia. (3rd January 2020) - Muche, Esileman Abdela; Ayalew, Mohammed Biset; Abdela, Ousman Abubeker
Abstract : Background. Patients with epilepsy are at an increased risk of poor quality of life. Purpose. We aimed at assessing the quality of life and its determinants among epileptic patients at University of Gondar Referral Hospital (UoGRH), Ethiopia. Methods. Institution based cross-sectional study was conducted on epileptic patients on follow up at UoGRH from January 15 to April 15, 2017. Information including socio-demographic profile and diagnosis was extracted from medical records and patients. Quality Of Life In Epilepsy-10 (QOLIE-10) tool was used to measure the quality of life. Independent t -test and one-way analysis of variance were used to look for factors associated with quality of life. The level of statistical significance was declared at P -value ≤ 0.05. Results. A total of 354 patients were included in the study and mean age was 29.1 ± 11.7 years. The mean QOLIE-10 score was 19.85. One hundred ninety-four (54.8%) of participants had a good quality of life. Being illiterate, unemployment, and presence of co-morbid medical condition were associated with poorer quality of life. Conclusion. Nearly half of the participants had a poor quality of life. Patients with co-morbidity, illiteracy, and unemployment should be given special emphasis in order to improve their quality of life.